MERANCANG PEMBELAJARAN ORGANISASI - Amiruddin, Siahaan; Makmur, Syukri; Budi, Ginting Setiawan (Universitas Islam Negeri (UIN) Sumatera Utara, 2022)
In a learning organization, it is necessary to design a learning organization. Designing Organizations we need to understand what a learning organization is. Learning organization is a concept where the organization is considered capable of continuously carrying out a self-learning process so that the organization has the speed of thinking and acting in response to various changes that arise. This study aims to examine the design of organizational learning. This research uses library research method. The data collection used in this study used factual analysis. So it is hoped that the research conducted can add insight and understanding about designing organizational learning.